+0  
 
0
265
1
avatar+771 

Solve. Express answer using interval notation where appropriate. Check for extraneous solutions.

\(\frac{3x}{x+1}+\frac{5}{x-2}=\frac{15}{x^2-x-2}\)

 May 13, 2018
 #1
avatar+27531 
0

Express \(x^2-x-2 \text{ as }(x+1)(x-2)\)

 

Multiply every term by \((x+1)(x-2) \text{ to get } 3x(x-2)+5(x+1)=15\)

 

Collect terms:  \(3x^2-x-10=0\)

 

Solve the quadratic to get \(x=-\frac{5}{3}\text{ and }x=2\)

 

2 is an extraneous solution (try substituting 2 into the original equation and see what you get!).

 May 13, 2018
edited by Alan  May 13, 2018

10 Online Users

avatar
avatar